Effective schools, school segregation, and the link with school achievement. Issue 3 (3rd July 2018) - Granvik Saminathen, Maria; Brolin Låftman, Sara; Almquist, Ylva B.; Modin, Bitte
ABSTRACT: This study examines whether 3 teacher-rated aspects of school effectiveness differ across school segregation profiles in Stockholm, and to what extent these indicators are associated with the academic achievement of 9th-grade students. Analyses were based on 2 cross-sectional data collections performed in 2014 and 2016, respectively (147 school units), one among teachers ( n = 2, 024) and the other among 9th-grade students ( n = 9, 151). Multilevel analysis was applied, estimating 2-level random intercept linear regression models. Results show that teachers' ratings of school leadership, teacher cooperation, and school ethos, as well as student-reported marks differ across school segregation profiles. Findings further reveal significant associations between these school effectiveness indicators and student performance, even when taking student family background and the school's student body composition into consideration. In part, these associations are also identified within segregation profiles. Moreover, results show that school ethos acts as a mediator between school segregation profile and student achievement.